2019
DOI: 10.1002/pc.25455
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mechanical property, thermal and electrical conductivity of natural rubber/graphene nanosheets nanocomposites

Abstract: Graphene nanosheets (GNs) were prepared by supercritical solvent intercalation method and cyclic stripping method under high pressure and stress. This “non‐chemical method” reduces impurities and avoids the destruction of graphene's intrinsic structure. In order to decrease the secondary stacking in processing, firstly GNs were dispersed in natural rubber (NR) latex to prepare NR/GNs concentrated master batch, and then combined with solid NR by mechanical blending. Since GNs have good dispersion in rubber matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The effect of GO on the tensile strength was the increase for a content of 1% and then a decrease to a value lower than that of NR at 5% [51]. The hybrid filler with a graphene layer, ultrafine carbon black, and the silane coupling agent led to a simultaneous and consistent increase of elongation and stress at break [57]. In the work with HSAG in synthetic poly(isoprene) a consistent decrease of both elongation and stress at break were found [44].…”
Section: Quasi-static Tensile Testsmentioning
confidence: 94%
See 1 more Smart Citation
“…The effect of GO on the tensile strength was the increase for a content of 1% and then a decrease to a value lower than that of NR at 5% [51]. The hybrid filler with a graphene layer, ultrafine carbon black, and the silane coupling agent led to a simultaneous and consistent increase of elongation and stress at break [57]. In the work with HSAG in synthetic poly(isoprene) a consistent decrease of both elongation and stress at break were found [44].…”
Section: Quasi-static Tensile Testsmentioning
confidence: 94%
“…When the GRM content was lower than 1%, the strain at break was substantially unaltered [51,54,55]. An increase of ε B was also reported, however with graphene nanosheets prepared through the oxidation of graphite worms and dispersed with the help of ultrafine carbon black and silane as coupling agent and adopting 4 phr as the maximum content of the filler [57]. In the case of composites based on synthetic isoprene rubber and the same HSAG used in the present work and prepared via melt blending, a consistent reduction of ε B was observed with a filler content up to 60 phr [44].…”
Section: Quasi-static Tensile Testsmentioning
confidence: 99%
“…-Possess same size scale as many biological molecules. [2,3,[12][13][14][15] Carbon nanotubes -Possess high thermal conductivity -Possess a remarkable electrical conductivity -Possess a remarkable mechanical property -Possess a large length-to-diameter ratio (aspect ratio) of higher than 1000 -The images of the actual space examination of nanotube have revealed a series of inter-stratum spacing -Single walled nanotube generally comprises of only 10 atoms near the circumference and the thickness of the tube is only one-atom thick [3,[16][17][18] Nanosheets -Exhibits high surface area that makes them advantageous for the fabrication of excellent reinforced polymeric composites -Their surfaces contain a large quantity of active oxygen-containing groups -Possess excellent mechanical and thermal conductivity properties -Possess excellent catalytic activities such as photo-/thermo-catalytic activity -Possess excellent thermal and electrical conductivity [5,6,[19][20][21] Nanofibers -Nanofibers are very small in size, which accords them outstanding physical and chemical properties -Possess huge surface area, high aspect ratio, and superior surface properties, which is responsible for their suitability for other technologies that need a smaller environment for chemical reaction to take place -Possess high pore volume and tight pore size that accords their suitability for an extensive range of filtration applications -Possess extreme adsorption capacity that has the capacity to improve many applications [4,[22][23][24] Meeting the demand and effectually making safe freshwater available is one of the utmost challenges globally. It forms a foremost menace to safe utilization of water, wellbeing, and trade and industry development [25].…”
Section: Nanomaterials Properties Referencesmentioning
confidence: 99%
“…Rubbers usually have low thermal conductivity about 0.10-0.23 W/m K. [5][6][7] Thermally conductive fillers such as boron nitride (BN) and carbon nanotube (CNT) are added into rubbers to prepare thermally conductive rubbers. [8][9][10] Liu et al found that the thermal conductivity of silicone rubber increased by 30% after the addition of 14% BN nanosheet.…”
Section: Introductionmentioning
confidence: 99%